Parametric resonance - Butikov, E.I. (Computing in science & engineering, 1999)
Computer simulation experiments are especially good tools for helping students understand basic principles of physics. In this a, I have developed a package of simulation programs called Physics of Oscillations. One of its programs is suited for examining the phenomenon of paramagnetic resonance in a linear system. The program simulates the parametric excitation of the rotary oscillations of a mechanical torsion-spring pendulum whose moment of inertia is subject to periodic variations. I discuss the conditions and characteristics of parametric resonance, including paramagnetic regeneration. Instructors and their students can also use the Physics of Oscillations package to explore other problems, such as ranges of frequencies within which parametric excitation is possible and stationary oscillations on the boundaries of these ranges. The simulation experiments complement the analytical study of the subject in a manner that is mutually reinforcing.